2000
DOI: 10.1128/iai.68.3.1282-1288.2000
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria tenellaInfection Induces Local Gamma Interferon Production and Intestinal Lymphocyte Subpopulation Changes

Abstract: The role of intestinal lymphocytes and gamma interferon (IFN-␥) production in protective immunity to Eimeria tenella infection was evaluated in two inbred strains of chickens (SC and TK) that display different patterns of susceptibility to coccidiosis. Oral inoculation of either strain with E. tenella led to parasite invasion of the intestinal cecum and cecal tonsils. Greater fecal oocyst shedding was seen in TK chickens. Flow cytometric analyses of cecal tonsil lymphocytes demonstrated greater numbers of CD4؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
50
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 46 publications
12
50
0
1
Order By: Relevance
“…In this experiment, dietary CLA did not change the percentage of duodenal CD4 + T lymphocytes and simultaneously had no effect on IFNγ expression, which is consistent with the viewpoint of Yun et al (2000). However, Laurent et al (2001) found that the IFNγ from CD8 + T lymphocytes was directly involved in the cellular immune response against coccidiosis in the test of broiler chicks infected with Eimeria tenella and Eimeria maxima.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this experiment, dietary CLA did not change the percentage of duodenal CD4 + T lymphocytes and simultaneously had no effect on IFNγ expression, which is consistent with the viewpoint of Yun et al (2000). However, Laurent et al (2001) found that the IFNγ from CD8 + T lymphocytes was directly involved in the cellular immune response against coccidiosis in the test of broiler chicks infected with Eimeria tenella and Eimeria maxima.…”
Section: Discussionsupporting
confidence: 77%
“…During the Eimeria tenella infection, the depletion of CD4 + T lymphocytes in the cecal tonsil of broiler chicks suppressed the IFNγ expression, while the depletion of CD8 + T lymphocytes enhanced the IFNγ expression, which is why Yun et al (2000) considered that IFNγ was derived from CD4 + T lymphocytes. In this experiment, dietary CLA did not change the percentage of duodenal CD4 + T lymphocytes and simultaneously had no effect on IFNγ expression, which is consistent with the viewpoint of Yun et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…There is a correlation between resistance to these diseases and early and higher IFN-γ production. A high level of IFN-γ production has also been shown in chicken strains that are resistant to coccidiosis [20,90,139]. These observations suggest that chicken lines with an enhanced IFN-γ response are more resistant to some viral and parasitic infections.…”
Section: Cytokinesmentioning
confidence: 76%
“…Similarly, a CD4 + cell dominated mucosal T cell response has been reported in chicken strains resistant to coccidiosis, whereas the susceptible lines have abundant CD8 + cells in the gut-associated lymphatic tissue [85,139]. In contrast, a CD8 + T cell biased response is predominant in chickens that are resistant to salmonella infection and have higher response to vaccination [10].…”
Section: T Cell Receptorsmentioning
confidence: 89%
See 1 more Smart Citation